Stations of the Cross : Adorno and Christian right radio - Apostolidis, Paul, 1965- (e-Duke books scholarly collection., 2000)
Analysis of the nationally broadcast radio program "Focus on the Family" that argues that the Christian right's popularity stems from its resistance to the increasing influence of market forces in the welfare state, the electoral system, and the.